Optimum technique of carotid artery reconstruction in her atherosclerotic lesion - V. V. Akhmetov; V. I. Dunaeva; F. A. Vryganov; S. V. Ordynets; I. P. Dudano (Исследования и практика в медицине)
Purpose of the study. Was to compare the early and long-term results of different variants of the classical KEAE.Materials and methods. In a retrospective study, we collected data on 1.242 patients who trans- ferred KEA from January 2011 to December 2019, using a patch was performed in 239 cases in 1003 — primary suture closure. We used 3 methods of arteriotomy closure with the use of a patch. There were 848 men and 394 women, the average age was 63.16 years, all of them were sympto- matic. Most patients had a transient disorder (49.2%) or ischemic stroke (50.8%). All patients had significant (moderate to severe) carotid stenosis. After the operation 5 (0.4%) patients had ischemic stroke, 1 (0.08%) had n. hypo-glossus damage, 3 (0.24%) had postoperative hematoma. The usual endarterectomy was performed without a shunt in all cases. All arteriotomies were mostly open. Early and late results of this procedure with a period of observation of at least 36 months were ana-lyzed: technical aspects of arteriotomy, features of restoration of the integrity of the vessel, changes in the "geometry" of the vessel, the use of zaplat. We studied the state of hemodynamics and complications in the early (30 days) and late postoperative period, the development of restenosis was compared between groups during the 36 months of observation. Results. When assessing the geometrical changes in the group with the patching, it was noted that the worst results were obtained using the technique with a U-shaped fixation suture on the distal part of the patch and the use of a wide patch. When using a narrow patch geometric changes in the width of the patch are the smallest. The main reason of the frequent geometrical changes in the dis-tal part of the patch was the patch wrapping inside the artery with the formation of a duplicate. The application of the modified technique of patch closure allowed to reduce the number of distortions in the operation area, to avoid the formation of artery stenoses in the place of patch imposition, to prevent changes in the bifurcation geometry of the internal carotid artery. The best results in the application of the primary edge suture were obtained by the method of closing the arteriotomy with the counter edge suture with the precision control of the application. The application of the U-shaped suture along the edges of the arteriotomy allowed avoiding deformations in this place. Con-trol of needle injection by means of straightening and lifting of the wall edge ensured absence of deformations in the suture.Conclusions. The post-CEAE closure technique affects the hemodynamic profile. Sewing patch-ing does not seem to create favorable flow dynamics. Consideration should be given to the elective use of the patch to improve disturbed flows. However, the linear precision suture remains the method of choice for suturing the arteriotomy.